2019
DOI: 10.1016/bs.ctdb.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A symbiont's guide to the germline

Abstract: Microbial symbioses exhibit astounding adaptations, yet all symbionts face the problem of how to reliably associate with host offspring every generation. A common strategy is vertical transmission, in which symbionts are directly transmitted from the female to her offspring. The diversity of symbionts and vertical transmission mechanisms is as expansive as the diversity of eukaryotic host taxa that house them. However, there are several common themes among these mechanisms based on the degree to which symbiont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 146 publications
(235 reference statements)
0
44
0
Order By: Relevance
“…Despite the differences in read-depths relative to the nuclear genome, our assembly includes nearly full coverage of the Wolbachia genome with few apparent misassemblies (Figure 3 and Supplementary Figure S2 ). Wolbachia in particular ( 33 ), and endosymbionts more generally ( 34 ), are frequently present in host somatic tissues, likely explaining the similar abundances of Wolbachia -derived reads across sequencing libraries prepared from different parts of the fly. This suggests that in addition to nearly complete nuclear genomes, our assembly method might also be a powerful tool for investigating individual's endosymbiont communities – a fundamental consideration in arthropod biology ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the differences in read-depths relative to the nuclear genome, our assembly includes nearly full coverage of the Wolbachia genome with few apparent misassemblies (Figure 3 and Supplementary Figure S2 ). Wolbachia in particular ( 33 ), and endosymbionts more generally ( 34 ), are frequently present in host somatic tissues, likely explaining the similar abundances of Wolbachia -derived reads across sequencing libraries prepared from different parts of the fly. This suggests that in addition to nearly complete nuclear genomes, our assembly method might also be a powerful tool for investigating individual's endosymbiont communities – a fundamental consideration in arthropod biology ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…The transmission routes of Rickettsia endosymbionts in biting midges are underexplored but can be informed by symbiont tissue localization. Although the maternal transmission of obligate symbionts is generally dependent on specialized cells (bacteriocytes), facultative (secondary) symbionts utilize various means to target the germ line ( 25 ). These can come in the form of cooption of yolk granules to gain entry into egg chambers via endocytosis (e.g., Spiroplasma in Drosophila melanogaster ) ( 39 ), or through the continuous association with the germ line during morphogenesis (e.g., Wolbachia in Drosophila spp.)…”
Section: Discussionmentioning
confidence: 99%
“…However, the route of migration to egg chambers by the symbiont is not clear and the tropisms to other tissues remain unexplored. Vertical transmission of nonobligate symbionts is achieved through diverse modes of germ line targeting ( 25 ). With certain Wolbachia strains of Drosophila spp., the symbiont localizes in the germ line stem cell niche continuously throughout development ( 26 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Often present in host germline stem cells (Russell et al 2019), Wolbachia has been shown to be capable of rescuing or maintaining this cell lineage in different host taxa. In D. melanogaster, the wMel strain of Wolbachia can rescue mutations in the germline stem cell maintenance genes sex lethal (sxl) (Starr and Cline 2002;Sun and Cline 2009) and bag of marbles (bam) (Flores et al 2015).…”
Section: A Known Wolbachia-induced Host Reproductive Phenotypes Andmentioning
confidence: 99%